Analysis of Identifying Company Operational System Development Utilizing the Quality Function Deployment - Nugraha, Evan; Sari, Rini Mulyani; Igorevna, Volkhonova Mariya (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: Performance is a key part in management's work in managing an organization. Employee performance is impacted by a variety of factors, both internal to the workforce and external to the government, firm, or organizational environment. One of the firms in Indonesia that felt the impact complained about performance issues, making it impossible to grow the company's management system. The majority of the issues arise from employee performance and a lack of knowledge about the company's operational management system, which limits the scope of optimizing the company operational.Methodology: The research method used qualitative research, data with questionnaire and brainstorming with respondents. for processing data with QFD method.Finding: The QFD calculations revealed and produces conclusions regarding the main identify priorities that must be taken by the company, including that employees must be able to offer good output/results for the organization, increase technical abilities in running work facilities while working, and be time disciplined.Conclusion: The QFD calculation's results showed that, for the respondent's level of interest, employees' ability to produce high-quality work products was the company's top priority, next motivate to apply time management finish tasks on schedule, and advance their technical proficiency and mental skills. In the meantime, the company's top focus in assisting staff members in meeting performance standards all.